Speech Facilitates the Categorization of Motions in 9-Month-Old Infants - Goldwater, Micah B.; Brunt, R. Jason; Echols, Catherine H. (Frontiers in Psychology, 2018)
Two experiments were used to investigate the influence of both native and non-native speech on the categorization of a set of an object’s motions by 9-month-olds. In Experiment 1, infants were habituated to a set of 3 object motions and tested with familiar and novel motions. Results of Experiment 1 show that infants were more likely to categorize the motion stimuli if they listened to either the native or non-native speech during the categorization process than if they listened to music or heard nothing at all. Results of Experiment 2 show that discrimination of the motions was not impaired by the presence of the labeling phrases. These results are consistent with a number of findings that report a unique influence of labels on categorization of static objects in infancy, and extend those findings to categorization of motions.